Second-harmonic generation as a probe for structural and electronic properties of buried GaP/Si(0 0 1) interfaces. (8th November 2018) - Brixius, K; Beyer, A; Mette, G; Güdde, J; Dürr, M; Stolz, W; Volz, K; Höfer, U
Abstract: Optical second-harmonic generation is demonstrated to be a sensitive probe of the buried interface between the lattice-matched semiconductors gallium phosphide and silicon with (0 0 1) orientation. Ex situ rotational anisotropy measurements on GaP/Si heterostructures show a strong isotropic component of the second-harmonic response not present for pure Si(0 0 1) or GaP(0 0 1). The strength of the overlaying anisotropic response directly correlates with the quality of the interface as determined by atomically resolved scanning transmission electron microscopy. Systematic comparison of samples fabricated under different growth conditions in metal–organic vapor phase epitaxy reveals that the anisotropy for different polarization combinations can be used as a selective fingerprint for the occurrence of anti-phase domains and twins. This all-optical technique can be applied as an in situ and non-invasive monitor even during growth.